The Effect of Top Management Commitment on Firm Performance through the Green Purchasing and Supplier Relationship Management in 3-Star Hotel Industry in Surabaya - Novia Chandra Tanuwijaya; Zeplin Jiwa Husada Tarigan; Hotlan Siagian (Master of Management, School of Business and Management, Petra Christian University, 2021)
The local government needs to facilitate the Hotel through industry regulations, and one of the requirements is the obligation of each Hotel to pay attention to environmentally friendly practices. This study investigates the effect of top management commitment on firm performance through green purchasing and supplier relationship management in the 3-star Hotel. This study used a Census survey for all 71 3-star Hotel domiciled in the City of Surabaya. Data collection used a questionnaire with a five-point Likert scale. Questionnaire distribution was conducted by email, social media, and direct delivery to the respondent. Sixty-one from seventy-one questionnaires, a response rate of 86%, were filled in duly and considered valid for further analysis. Data analysis used the partial least square technique by utilizing Smart PLS. The result of the analysis demonstrated that top management commitment affects supplier relationship management by path coefficient of 0.544. Top management commitment affects firm performance with path coefficient of 0.281. However, this study indicated that top management commitment does not affect green purchasing. Furthermore, supplier relationship management has a significant effect on green purchasing with path coefficient of 0.391. Similarly, supplier relationship management also affects firm performance with a path coefficient of 0.377. Finally, Green purchasing significantly improves firm performance with a path coefficient of 0.226. This work provides a new insight for the manager on how to increase firm performance in the context of supply chain management. This study could contribute to enriching the current research in supply chain management.